Strategi Pola Komunikasi Organisasi Dan Pengelolaan Informasi Digital Melalui Saluran Media Sosial Guna Meningkatkan Efesiensi Dalam Berkomunikasi - Aldo Alizamardi; Muhammad Zaikal Alfarizi; Aditya Rizki Al Fakhri; Ahmad Rafii Am (CV. ITTC INDONESIA, 2025)
This study examines the transformation of organizational communication patterns from a conventional bureaucratic model to a social media-based digital system to improve operational efficiency. Integrating Joseph A. Devito's communication pattern theory and Littlejohn & Foss's organizational dimensions, this study analyzes the effectiveness of the